Redox‐engineering enhances maize thermotolerance and grain yield in the field. Issue 9 (25th June 2022) - Sprague, Stuart A.; Tamang, Tej Man; Steiner, Trevor; Wu, Qingyu; Hu, Ying; Kakeshpour, Tayebeh; Park, Jungeun; Yang, Jian; Peng, Zhao; Bergkamp, Blake; Somayanda, Impa; Peterson, Morgan; et al.
Summary: Increasing populations and temperatures are expected to escalate food demands beyond production capacities, and the development of maize lines with better performance under heat stress is desirable. Here, we report that constitutive ectopic expression of a heterologous glutaredoxin S17 from Arabidopsis thaliana ( AtGRXS17 ) can provide thermotolerance in maize through enhanced chaperone activity and modulation of heat stress‐associated gene expression. The thermotolerant maize lines had increased protection against protein damage and yielded a sixfold increase in grain production in comparison to the non‐transgenic counterparts under heat stress field conditions. The maize lines also displayed thermotolerance in the reproductive stages, resulting in improved pollen germination and the higher fidelity of fertilized ovules under heat stress conditions. Our results present a robust and simple strategy for meeting rising yield demands in maize and, possibly, other crop species in a warming global environment.